Perlindungan Pelaku Usaha Jasa Transportasi Setelah Larangan Mudik 2021 Karena Covid-19 - Vani Rizky Amellya; Ro’fah Setyowati; Novira Maharani Sukma (Notarius, 2021)
Humans need means of transportation to meet their needs. One element that is closely related to transportation is the transportation service manager (business actor). Transportation service business actors generally reap profits when there are long holidays and Lebaran homecoming. However, in 2021, going home for Eid is prohibited due to the Corona Virus. Two issues that will be discussed are how to protect transportation business actors in Indonesia in general? and what should be the role of the government in protecting transportation service business operators during the Covid-19 pandemic? The method used in discussing this article is a normative method using 3 approaches, namely the approach to legislation, concepts, and cases whose conclusions are: first, the protection of transportation business actors in Indonesia in general can be seen from the UUPK Law and the LLAJ Law. Second, the role of the government in protecting transportation service business actors during the Covid-19 pandemic can be done in various ways, namely: providing subsidies to transportation service business actors; accelerate the provision of free vaccines for workers in the transportation sector and the general public; and does not issue overlapping and arbitrary statements and rules.Keyword: protection; businessmen; transportation; services; covid-19AbstrakManusia memerlukan alat transportasi untuk menggalang kebutuhannya. Salah satu unsur yang erat dalam transportasi tersebut adalah pengelola jasa transportasi (pelaku usaha). Pelaku usaha jasa transportasi umumnya panen keuntungan ketika adanya libur panjang serta mudik lebaran. Namun, pada tahun 2021 ini, mudik lebaran dilarang karena adanya Virus Corona. Dua permasalahan yang akan dibahas adalah bagaimana perlindungan pelaku usaha trsanportasi di Indonesia secara umum? dan bagaimana seharusnya peran pemerintah dalam melindungi pelau usaha jasa transportasi saat pandemi Covid-19? Metode yang digunakan dalam membahas artikel ini adalah metode normatif menggunakan 3 pendekatan yaitu pendekatan perundangan, konsep, dan kasus yang kesimpulannya berupa: pertama, perlindungan pelaku usaha trsanportasi di Indonesia secara umum dapat dilihat dari UUPK dan UULLAJ. Kedua, peran pemerintah dalam melindungi pelaku usaha jasa transportasi saat pandemi Covid-19 dapat dilakukan dengan berbagai cara, yaitu: pemberian subsidi kepada para pelaku usaha jasa transportasi; percepatan pemberian vaksin gratis bagi pekerja di bidang transportasi dan masyarakat umum; dan tidak mengeluarkan statement dan aturan yang tumpang tindih dan berubah-ubah.Kata Kunci: perlindungan; pelaku; usaha; transportasi; covid-19